1970
DOI: 10.1001/archneur.1970.00480290033004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid and Cranial Sinus Pressures

Abstract: PRESSURE has repeatedly been demonstrated to be an important factor in bulk absorption of cerebrospinal fluid (CSF). The dependence of absorption on pressure was shown to be linear above a critical threshold pressure and thereafter over a wide pressure range.1-4 A similar, although

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For this to be the case, dural sinus pressure must remain constant while the intracranial CSF pressure increases, which has been demonstrated to be true for cats and dogs (Weed and Flexner, 1933;Weed, 1935;Bering, 1958;Shulman, Yarnell, and Ransohoff, 1964;Shulman, 1965), as well as most adult humans so tested (author's unpublished data). But other reports leave little doubt that in some infants with hydrocephalus (Shulman and Ransohoff, 1965;Norrell, Wilson, Howieson, Megison, and Bertan, 1969), adults with subdural haematomas (Osterholm, 1970) and in hydrocephalic animals (Shulman et al, 1964; and Ransohoff, 1970), the dural sinus pressure does…”
Section: Discussionmentioning
confidence: 98%
“…For this to be the case, dural sinus pressure must remain constant while the intracranial CSF pressure increases, which has been demonstrated to be true for cats and dogs (Weed and Flexner, 1933;Weed, 1935;Bering, 1958;Shulman, Yarnell, and Ransohoff, 1964;Shulman, 1965), as well as most adult humans so tested (author's unpublished data). But other reports leave little doubt that in some infants with hydrocephalus (Shulman and Ransohoff, 1965;Norrell, Wilson, Howieson, Megison, and Bertan, 1969), adults with subdural haematomas (Osterholm, 1970) and in hydrocephalic animals (Shulman et al, 1964; and Ransohoff, 1970), the dural sinus pressure does…”
Section: Discussionmentioning
confidence: 98%
“…Later, Adolph et al (1967) demonstrated in an experimental study, where the effects of right atrial and left ventricular cardiac events were dissociated, that., depending on systemic haemodynamic conditions, CSF pressm'e waves are either venous or arterial in type. 1966, Guthrie et al 1970, Sahar et al 1970, Lowell et al 1971, Kaste et M. 1972, no simultaneous recordings of cerebrospinal pressure waves and cerebral venous pressure variations under physiological conditions were reported in previous neurosurgieal and physiological literature. 1964, Langfitt eta].…”
Section: Discussionmentioning
confidence: 99%
“…Special interest is focussed on the pressure relationship between CSFP and SSP, because' the pressure gradient between the subarachnoid space and the sagittal sinus apparently plays an important role in CSF resorption (Mortensen et al 1934, Weed 1935, Bering et al 1959, 1963, Welch et al 1960, Shulman et al 1964, Davson 1970, Sahar et al 1970. Special interest is focussed on the pressure relationship between CSFP and SSP, because' the pressure gradient between the subarachnoid space and the sagittal sinus apparently plays an important role in CSF resorption (Mortensen et al 1934, Weed 1935, Bering et al 1959, 1963, Welch et al 1960, Shulman et al 1964, Davson 1970, Sahar et al 1970.…”
Section: Introductionmentioning
confidence: 99%
“…It is the outflow for venous blood and the site of reabsorption for CSF. It maintains a pressure lower than the ICP under most physiological conditions [22][23][24][25][26][27]. In addition, in the model the spinal thecal sac compartment is interconnected to the intracranial space through the link between the cranial and spinal subarachnoid spaces.…”
Section: Methodsmentioning
confidence: 99%